Management of multiple magnetic foreign body ingestion in pediatric patients - Yi Jin; Zhigang Gao; Yuebin Zhang; Duote Cai; Di Hu; Shuhao Zhang; Jianhua Mao (BMC Pediatrics, 2022)
Abstract Background Multiple magnetic foreign body ingestion in children is increasingly common and can cause serious injury. The present study aimed to analyze the clinical features of such cases and summarize treatment experiences. Methods A retrospective survey of 91 patients in the Children’s Hospital, Zhejiang University School of Medicine with magnetic foreign body ingestion from October 2018 to October 2021 was performed, the data were collected including the clinical information of the patients, treatment details, and prognosis. Results Twenty-two (24.2%) patients were conservatively treated, with the foreign bodies discharged through the anus, 31 (34.1%) underwent laparoscopic surgery, including 18 cases converting from laparoscopic surgery to laparotomy, and 38 (41.8%) underwent laparotomy. In 13 (14.3%) patients, the foreign bodies were partially removed by gastroscope. The remaining foreign bodies were removed by laparoscopy in six patients, including three cases converting from laparoscopy to laparotomy, by laparotomy in four patients, and by conservative treatment in three patients. Conclusions Multiple magnetic foreign body ingestion can cause significant harm to patients and different clinical techniques must be used for patients in different situations to reduce the harm to children.